Correlation Between Local Air Temperature and the COVID-19 Pandemic in Hubei, China - Liu, Li (Frontiers in Public Health, 2021)
Objective: To clarify the correlation between temperature and the COVID-19 pandemic in Hubei. Methods: We collected daily newly confirmed COVID-19 cases and daily temperature for six cities in Hubei Province, assessed their correlations, and established regression models. Results: For temperatures ranging from -3.9 to 16.5 °C, daily newly confirmed cases were positively correlated with the maximum temperature 0–4 days prior or the minimum temperature 11–14 days prior to the diagnosis in almost all selected cities. An increase in the maximum temperature four days prior by 1 °C was associated with an increase in the daily newly confirmed cases ( 129) in Wuhan. The influence of temperature on the daily newly confirmed cases in Wuhan was much more significant than in other cities. Conclusion: Government departments in areas where temperatures range between -3.9 and 16.5 °C and rise gradually must take more active measures to address the COVID-19 pandemic.